Endovascular Treatment of Post Type A Chronic Aortic Arch Dissection With a Branched Endograft: Early Results From a Retrospective International Multicenter Study. Issue 5 (8th May 2021) - Verscheure, Dorian; Haulon, Stéphan; Tsilimparis, Nikolaos; Resch, Timothy; Wanhainen, Anders; Mani, Kevin; Dias, Nuno; Sobocinski, Jonathan; Eagleton, Matthew; Ferreira, Marcelo; Schurink, Geert Willem; Modarai, Bijan; et al.
Abstract : Objective: The objective of this study was to evaluate the outcome of endovascular aortic arch repair for chronic dissection with a custom-made branched endograft. Background: Acute type A aortic dissections are often treated with prosthetic replacement of the ascending aorta. During follow-up, repair of an aneurysmal evolution of the false lumen distal to the ascending prosthesis can be a challenge both for the surgeon and the patient. Methods: We conducted a multicenter, retrospective study of consecutive patients from 14 vascular units treated with a custom-made, inner-branched device (Cook Medical, Bloomington, IN) for chronic aortic arch dissection. Rates of in-hospital mortality and stroke, technical success, early and late complications, reinterventions, and mortality during follow-up were evaluated. Results: Seventy consecutive patients were treated between 2011 and 2018. All patients were considered unfit for conventional surgery. In-hospital combined mortality and stroke rate was 4% (n = 3), including 1 minor stroke, 1 major stroke causing death, and 1 death following multiorgan failure. Technical success rate was 94.3%. Twelve (17.1%) patients required early reinterventions: 8 for vascular access complication, 2 for endoleak correction, and 2 for pericardial effusion drainage. Median follow-up was 301 (138–642) days. During follow-up, 20 (29%) patients underwent secondary interventions: 9 endoleak corrections, 1 open repair for prosthetic kink, and 10 distal extensions of the graft to the thoracic or thoracoabdominal aorta. Eight patients (11%) died during follow-up because of nonaortic-related cause in 7 cases. Conclusions: Endovascular treatment of aortic arch chronic dissections with a branched endograft is associated with low mortality and stroke rates but has a high reintervention rate. Further follow-up is required to confirm the benefits of this novel approach.